An investigation of support services available for black female owners of bed & breakfasts in Makhanda - Mdluli, Lukhona Silubonile (Rhodes University, Faculty of Commerce, Rhodes Business School)
Over the last 26 years, the South African government has committed to SMME development. To do this, policies and support institutions were put in place which would create a favourable environment for SMME development. This was particularly important as after 1994, when the South African economy was re-integrated into global markets after years of having sanctions imposed against the country as a result of the apartheid system. The tourism industry was identified as one of the key economic drivers which would strengthen the economy and assist in job creation, especially since South Africa would be able to attract international tourists. Further, it created the opportunity for new participants to enter the industry, including black entrepreneurs who previously could not enter the industry as a result of the apartheid laws. The opening up of the country to international markets and the focus on the tourism industry also presented the opportunity for new forms of tourism to be explored including township tourism, which gave rise to the black-owned bed & breakfast sector. Over time, it has become evident that black entrepreneurs in this sector are facing a number of challenges, in spite of the pro-SMME policies and support institutions that are in place. Because this study seeks to investigate the support services available for black female bed & breakfast owners in Makhanda, a qualitative research approach using the interpretative theoretical framework was applied. By using semi-structured interview questions, to establish what challenges do black female bed and breakfast owners face the researcher was able to respond to the following; what participants identify as their needs; and whether they are able to access the support services that are made available by the Government. Results indicated that the majority of entrepreneurs have difficulty accessing funding to develop their businesses. The seasonality of Grahamstown/ Makhanda tourism businesses has its pros and cons for tourism entrepreneurs. Despite efforts by government to transform the tourism industry, black female entrepreneurs in this industry still experience a myriad of challenges, including passive racism. Insufficient institutional support and inaccessible support services for women have made it difficult to manage in this this environment. Thus, a recommendation is put forward for female focused entrepreneurship policy, which is more responsive in terms of a judicial and legal system(s) aimed at addressing women's particular needs and challenges.
Keywords: Bed and breakfast accommodations -- South Africa -- Makhanda; Businesspeople, Black -- South Africa -- Makhanda; Business enterprises, Black -- South Africa -- Makhanda; Women-owned business enterprises -- South Africa -- Makhanda; Government aid to small business -- South Africa; Small business -- South Africa -- Makhanda; Racism -- South Africa -- Makhanda; Businesswomen -- South Africa -- Makhanda